Inclusion of dried small fish in the ICDS Supplementary Nutrition Programme Pilot Study in Odisha, India - Chadag, Vishnumurthy Mohan (2022)
Aquatic foods, especially fish, have long been regarded as a rich source of animal protein and micronutrients, and, therefore, considered a key constituent of nutritious diets. With a common goal of enhancing the nutritional outcomes from aquatic foods and to assist in accelerating progress on reducing malnutrition in hard-to-reach tribal communities, USAID and WorldFish along with other partner organizations such as Fisheries and Animal Resources Development (FARD) and Indian Council of Agricultural Research and Central Institute of Fisheries Technology (ICAR-CIFT) collaborated with the Women and Child Development Department and Mission Shakti (WCD & MS) of the government of Odisha to pilot the inclusion of small fish and fish-based products in the SNP. Subsequently, a Memorandum of Understanding (MoU) was signed by WorldFish and WCD & MS on 10th November 2020. Specifically, this piloting involves the inclusion of small fish powder in HCM for 3-6-year-old children and dried small fish in THR for Pregnant and Lactating Women (PLW) and 14-18-year-old Adolescent Girls (AG). Based on an approved Standard Operating Procedure (SOP), the pilot has been implemented in 50 Anganwadi Centers of Kaptipada block, Mayurbhanj district and the duration of the project was 6 months starting from April 2021 to September 2021. Based on feedback and acceptance received from the community of the inclusion of dried fish-based products in SNP, as well as enhanced understanding on nutritional outcomes from aquatic foods congregated from the pilot, this nutrition-sensitive approach can be adopted and scaled to ameliorate the undernutrition scenarios across Odisha.